Reviewer Acknowledgements for Journal of Education and Training, Vol. 11, No. 2 - Wang, Dora (Journal of Education and Training, 2024)
Journal of Education and Training (JET) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JET publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 11, Number 2 F. Elgamal, Faculty of Specific Education- Computer Science Dep.Mansoura University, Egypt Bryan Spiegelberg, Rider University, USA John Cowan, Edinburgh Napier University, Scotland Jukdao Potisaen, Rajabhat Mahasarakham University, Thailand Lazarus Ndiku Makewa, University of Eastern AfricaBaraton, Kenya Montasser Mohamed AbdelWahab Mahmoud, Imam Abdulrahman bin Faisal University, Saudi Arabia Paola Molteni, Università Cattolica del Sacro Cuore di Milano, Italy Shijuan Liu, Indiana University of Pennsylvania, USA Dora Wang Editorial Assistant Journal of Education and Training Macrothink Institute —————————————– 5348 Vegas Dr.#825 Las Vegas Nevada 89108 United States Phone: 1-702-953-1852 ext.534 E-mail 1: jet@macrothink.org E-mail 2: jet@macrothink.com Website: http://jet.macrothink.org